Integrasi Kurikulum Berbasis Cinta Dan Teori Multiple Intelligences Dalam Pembelajaran IPA Di Madrasah Ibtidaiyah - Khairunnisa; Ayu Tri Darma Ramadhani; Miftahul Jannah (CV. Multi Kreasi Media, 2025)
Education at the Madrasah Ibtidaiyah (MI) level currently faces significant challenges in balancing cognitive mastery with holistic character building amidst moral crises and intolerance. This study aims to elaborate on the integration of the 2025 Love-Based Curriculum (KBC) and Howard Gardner's theory of Multiple Intelligences in Natural Science (IPA) learning at MI. The method employed is library research, using content analysis and descriptive-synthesis techniques on KBC policy documents and literature related to multiple intelligences. The results indicate that the synergy between KBC and Multiple Intelligences creates a holistic and inclusive science learning ecosystem. The